Answer:
Step-by-step explanation:
(x+2)(3x-3)
= 3x^2 -3x + 6x - 6
= 3x^2 + 3x - 6
Answer:
y = -4
Step-by-step explanation:
First, let's find the slope. Since the line is horizontal, it's slope has to be 0 (this is because slope = rise/run, there is no "rise" in a horizontal line therefore the slope is 0)
Now, we need to find the y-intercept. This is where the line intercepts the y-axis. Looking at the graph, the line intercepts the axis at (0,-4), therefore the y-intercept is -4.
The equation would be:
y=0x-4
y=-4
B. No, because it fails the vertical line test.
Answer: y = -3/2x + 5
Step-by-step explanation:
Answer:
a = 2500mm
b = 5km
c = 2e+7
Step-by-step explanation: